若f(x)=x(x-1)(x-2)(x-3)(x-4),则f'(0)=?
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 03:16:45
若f(x)=x(x-1)(x-2)(x-3)(x-4),则f''(0)=?若f(x)=x(x-1)(x-2)(x-3)(x-4),则f''(0)=?若f(x)=x(x-1)(x-2)(x-3)(x-4),
若f(x)=x(x-1)(x-2)(x-3)(x-4),则f'(0)=?
若f(x)=x(x-1)(x-2)(x-3)(x-4),则f'(0)=?
若f(x)=x(x-1)(x-2)(x-3)(x-4),则f'(0)=?
解由f(x)=x(x-1)(x-2)(x-3)(x-4)
得
f'(x)=[x(x-1)(x-2)(x-3)(x-4)]'
=x'[(x-1)(x-2)(x-3)(x-4)]+x[(x-1)(x-2)(x-3)(x-4)]'
=[(x-1)(x-2)(x-3)(x-4)]+x[(x-1)(x-2)(x-3)(x-4)]'
故f'(0)=(0-1)(0-2)(0-3)(0-4)+0×[(0-1)(0-2)(0-3)(0-4)]'
=(-1)(-2)(-3)(-4)
=24
若f(x)满足f(x)-2f(1/x)=x,则f(x)=?
若F(x)满足f(x)+2f(1/x)=x,则f(x)=
f(x)=x^2+x (x
f(x)={2x+1,x
f(x)={1+x/2,x
f(x)=(x-1)/(x+2)
若函数f(x)满足f(x)+2f(1/x)=5x+4/x,则f(x)=
f(x)+f((x-1)/x)=2x; x!=0,1; 求f(x)
f(x)+f[(x-1)/x]=2x x不等于0,1.求f(x).
max{f(x),g(x)}=1/2(f(x)+g(x)+|f(x)-g(x)|
若F(X-1/X)=X^2+1/X^2,求F(X-1)
若f(x)=(x-1)(x-2)...(x-2010)(x-2011),则f'(1)=
若f(1/x)=x+根号1+x^2 (x>0),则f(X)=
若f(2x+1)=x*x+x,则f(x)
若一次函数f(x) 满足f[f(x)]=1+2x 求f(x)
f(X)=f(X+2)(x
函数F(x)=2x,x>=1,F(x)=x^2,x
f(x)=|x+2|+|x-2|值域 f(x)=|x-2|-|x+1|值域